From Petersburg to Shipka via Mount Athos: Slavic Saints on the Shipka Iconostasis - Ivanka Gergova (Slavia Meridionalis, 2024)
From Petersburg to Shipka via Mount Athos: Slavic Saints on the Shipka Iconostasis